El aporte del sector agrícola al crecimiento Económico del Ecuador en el período 1980-2019. - Robles Ayala, Alexandra Maribel (2022)
Ecuador is characterized by having four regions: Coast, Sierra, Amazon and Galapagos Island. Regarding the agricultural sector, each of these regions has its representative products that through history have played a fundamental role in the economic development of the country. According to figures from the Central Bank of Ecuador, the agricultural sector contributes 8% to the country's total annual production (GDP), and it also one of the main generators of employment in the rural sector, generating 2.2 million jobs in the country. year 2019. Therefore, this research aims to evaluate the incidence of the agricultural sector on the economic growth of Ecuador in the period 1980-2019. In the present research work, data from the World Bank (2020) were taken, it is worth made that a regression will be carried out where the dependent variable is the Gross Domestic Product and the independent variable is agriculture, additionally three control variables are included: expenditure government, gross capital formation and the labor force, applying time series. The research work were made under the Generalized Least Squares (GLS) methodology that determines the relationship of the variables, likewise a Vector Error Correction (VEC) model was applied which helped to determines the long-term equilibrium relationship. The results obtained showed that the agricultural sector and economic growth have a positive and statistically significant relationship. It is recommended that the government, and more specifically the Ministry of Agriculture, Livestock, Aquaculture and Fisheries (MAGAP), manage projects giving priority to agricultural areas with the highest potential for development.